An Analysis Of Perceived Usefulness, Perceived Ease Of Use, And Perceived Security On The Intention To Use Qris In Malang City - Saleh, Ibadurrahman; Putri, Intan Lifinda Ayuning (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This research quantitatively determines whether perceived usefulness, perceived ease of use, and perceived security affect the intention to use QRIS in Malang City. Bank Indonesia, as the regulator of financial and payment regulations, has issued a new payment instrument, QRIS, as a standardization of digital payment instrument applications based on QRCode. This research involves 105 respondents of established criteria, including age, gender and job, and data collected through questionnaires distributed through Google Forms. The data obtained are analysed by the Partial Least Square Structural Equation Modeling (PLS-SEM) processed by SmartPLS software. The results of this research exhibit that perceived usefulness, perceived ease of use, and perceived security affect the intention to use QRIS in Malang City. This research supports the TAM theory and can be a consideration for digital financial service providers in developing QRIS to provide added value to their services to consumers.